KINERJA TUTOR DALAM PELAKSANAAN PEMBELAJARAN KESETARAAN PAKET C DI PUSAT KEGIATAN BELAJAR MASYARAKAT (PKBM) KECAMATAN RUMBAI PESISIR KOTA PEKANBARU - Miranti, Amanda; Jas, Jaspar; Maemunaty, Tity (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This studyaims to determinethe high performance tutors learning in the implementation of the equality package C in community learning center (PKBM) Rumbai Pesisir Districts of Pekanbaru City.The research question guiding this study is: how high the level of performance in the implementation of tutors learning equality package C in community learning center (PKBM) Rumbai Pesisir District of Pekanbaru City?. This is a descriptive study, data were collected using a questionnaire shaped instrument number 43 point statement. Once tested, the questionnaire is valid as much as 36 grains, and is invalid as much as 7 grains. Overall declared valid instrument with "rhitung = 0.444 means quite high validity. The population in this study was 36 C The package tutor a sample is taken using the sampling using sampling methods saturated / census with an overall sampling, to determine the number and valid items then can be tested by using a questionnaire prior to the tutor package C at PKBM Rumbai Pesisir District of the city of Pekanbaru. Based on the research findings obtained tutor performance in the implementation of learning equality package C in community learning center (PKBM) District of Rumbai Pesisir Pekanbaru based learning respondents planning performance level high at 75.82% and the performance level of respondents was lower by 24.15% , By implementing learning activities respondents high performance levels by 78% and respondents low performance levels by 22%. Based on respondents' assessment of learning that implementing high performance level of 77% and a low performance level of respondents by 23%. By conducting a follow-up study respondents that high performance levels of 68% and a low performance level of respondents by 32%.Key words: performance, tutors, learning implementation, equality package C, the center of learning activities (PKBM)2